Meningkatkan Motivasi dan Hasil Belajar Siswa dengan Menggunakan Media Digital (YouTube dan Game Online) pada Materi Literasi Digital untuk Kemajuan Bangsa di SMP Sunan Giri Kota Probolinggo - Dzaky Isyuniandri; Alfiatus Syarofah; Halimah Halimah; Indani Khoirun Nisak; Syamriba Ardila (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This Classroom Action Research (PTK) was motivated by the low interest of students in Civics subjects. This is thought to be due to a lack of adequate reference sources, which makes students have to write a lot of study material which then makes them feel bored and boring. This Classroom Action Research (PTK) aims to increase student motivation and learning outcomes by using digital media (YouTube and Online Games) on the material "Digital Literacy for Student Progress" at Sunan Giri Middle School, Probolinggo City. The benefits of Classroom Action Research (PTK) are: it can provide information about the causes of students' low interest in Civics subjects as well as ways to increase student motivation. Classroom Action Research (PTK) can provide greater opportunities for students to gain knowledge by using media. digital in the learning process, so that it has an impact on improving student learning outcomes, besides that it can also be used as input material in an effort to increase student motivation and learning outcomes in Civics subjects. Thus, students' interest in learning about Civics subjects increases. Classroom Action Research consists of 2 cycles. Data from this research was obtained from teachers (observers) and students through observation, tests and documentation. Based on research data from cycle I to cycle II, data was obtained that students' interest and learning outcomes in the learning process through digital media (YouTube and Online Games) had increased significantly from previous learning which used the summarizing method. So the conclusion is that the application of digital media (YouTube and Online Games) can increase student interest and learning outcomes in Civics subjects at Sunan Giri Middle School, Probolinggo City.